A study of the temporal and spatial variations in the suitability of the environment in Chinese cities for tourism and in strategies for optimizing the environment. Issue 1 (31st December 2022) - Li, Ying; Zhang, Shuhui; Han, Jingting; Zhao, Yi; Han, Quan; Wu, Liyun; Wang, Xin; Qiu, Ziyi; Zou, Tongqian; Fan, Cheng
ABSTRACT: With the aim of guaranteeing the interests and health of tourists, this study comprehensively evaluates the suitability of the environment in different cities in China for tourism by considering the impacts of climate, vegetation and environmental factors on health. The Universal Thermal Climate Index (UTCI), total precipitation (PREC), Vegetation Leaf Area Index (LAI), concentration of particulate matter with a diameter of less than 2.5 μm (PM2.5 ), and the downward UV radiation at the surface (UVB) are used as indices. In addition, the Delphi–AHP–TOPSIS algorithm is introduced and is used for the comprehensive evaluation of the environmental suitability of 684 cities in China for tourism in 2019. It is found that Chinese cities vary greatly in terms of the suitability of their environments for tourism. Among the factors that affect the environmental suitability, the LAI is important, with an increase in the LAI generally being advantageous. In contrast, an increase in the PM2.5 concentration is a key factor that limits the environmental suitability of an area. Thus, urban landscaping and control of the atmospheric quality are essential and effective ways of improving the suitability of the environment of cities in China for tourists.